Head and neck reconstruction using infrahyoid myocutaneous flaps - Tincani, Alfio José; Negro, André Del; Araújo, Priscila Pereira Costa; Akashi, Hugo Kenzo; Neves, Flavia Silva Pinto; Martins, Antônio Santos (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: The use of pedicled myocutaneous flaps in head and neck reconstruc- tion is widely accepted. Here we describe our experience with infrahyoid flaps (IHFs) employed to cover surgical defects in the oral cavity and oropharynx in patients with benign and malignant tumors. The aim was to evaluate the success rate for infrahyoid myocutaneous flap procedures performed at a single institution. DESIGN AND SETTING: Retrospective study, at the Head and Neck Surgery Service, Unicamp. METHODS: Fourteen IHFs were used to recon- struct surgical defects in eleven men (78.5%) and three women (21.5%) with a mean age of 66.4 years. The anterior floor of the mouth was reconstructed in nine patients (64.2%), the base of tongue in three (21.4%), the lateral floor in one (7.1%), and the retromolar area (7.1%) in one. Thirteen patients (92.8%) had squamous cell carcinoma (SCC) and one (7.2%) ameloblastoma. The disease stage was T3 in eight (61.5%) of the SCC cases and T4 in five (38.5%). RESULTS: No patient presented total flap loss or fistula. The most common complication was epidermolysis, which delayed the beginning of oral ingestion. The patients with SCC received postoperative radiotherapy without major consequences to the flap. CONCLUSION: IHF is a safe and reliable procedure for reconstructing head and neck surgical defects. Due to its thinness and malleability, its use for oral cavity and oropharynx defects provides favorable cosmetic and functional outcomes. Complications, when present, are easy to manage.